Winners And Losers In Coronavirus Times: Financialisation, Financial Chains and Emerging Economic Geographies of The Covid-19 Pandemic - Sokol, Martin (My University, 2020)
This paper has two interrelated aims. First, it attempts to sketch a preliminary map of economic winners and losers to highlight the emerging economic geographies of the coronavirus pandemic. Second, it aims to explore the links between these emerging economic geographies and the processes of 'financialisation', drawing on the concept of 'financial chains'. Regarding the first aim, the paper argues that the pandemic-induced crisis will exacerbate social inequalities and deepen uneven development at multiple geographical scales. Regarding the second aim, the paper argues that the 'financialisation' perspective in general, and the concept of 'financial chains' in particular, provide useful insights into the crisis and its uneven effects, by shedding light on the complex web of flows of value and power relations established/emerging between the prospective winners and losers. It also highlights the prominent role of debt and debt-based financial chains in shaping economic geographies in times of major global crisis. Keywords: Financialisation; crisis; debt; economic geography; financial chains; pandemic.
PUBLISHED
DOI: 10.1111/tesg.12433
Keywords: Financialisation; Financial crisis; Debt; Economic geography; Financial chains; Pandemic